RANCANG BANGUN SISTEM DESTILASI LIMBAH THINNER MENGGUNAKAN METODE FUZZY - Wijaya, Ikhlasul Rizqi; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems (JCONES), 2016)
Many of small and medium a recycler company of waste materials based on mixture of paint and thinner forms. The problems in this company is still using the traditional method for the waste distillation process. Solution to these problems is the automation of temperature control for the heating process thinner waste by using fuzzy method for fuzzification process, setting rules and defuzzification. The results obtained from the application of this method is reusable thinner. The tools that used in this application is the microcontroller as the brain of the machine control, thermocouple for detecting temperature values and also a motor functions as a regulator of the amount of fire coming out.